(untitled) (Global Journal of Science Frontier Research, 2015)
Sustainable farming systems are required to allow crops to better cope with the simultaneous multiple stresses that they grow under or are likely to be exposed to under future climate change. Fungal endophytes could form part of the solution. They have been shown to improve important agronomic traits under a single stress, but few studies have investigated the impact of endophytes on growth or disease resistance when exposed to multiple stresses. We compared the performance of the barley cultivar Propino when inoculated with five fungal root endophytes, either individually or combined, derived from wall barley (Hordeum murinum) and grown in optimal conditions (OC) and under a combined drought, heat, nutrient and pathogen stress (MS). We found a greater endophyte-induced improvement in important agronomic traits in the MS plants compared with the OC plants. For the MS plants only 13% of the controls survived to the end of the experiment compared with 80% of the endophyte treatments.